A comparison of primary oesophageal squamous epithelial cells with HET-1A in organotypic culture - Underwood, Timothy J.; Derouet, Mathieu F.; White, Michael J.; Noble, Fergus; Moutasim, Karwan A.; Smith, Eric; Drew, Paul A.; Thomas, Gareth J.; Primrose, John N.; Blaydes, Jeremy P. (Biology of the cell, 2010)
Background Information. Carcinoma of the oesophagus is the sixth leading cause of cancer death in the western world and is associated with a 5‐year survival of less than 15%. Recent evidence suggests that stromal—epithelial interactions are fundamental in carcinogenesis. The advent of co‐culture techniques permits the investigation of cross‐talk between the stroma and epithelium in a physiological setting. We have characterized a histologically representative oesophageal organotypic model and have used it to compare the most commonly used squamous oesophageal cell line, HET‐1A, with primary oesophageal squamous cells for use in studies of the oesophageal epithelium in vitro. Results. When grown in an organotypic culture with normal fibroblasts, the oesophageal carcinoma cell lines OE21 (squamous) and OE19 (adenocarcinoma) morphologically resembled the tumour of origin with evidence of stromal invasion and mucus production, respectively. However, HET‐1A cells, which were derived from normal squamous oesophageal cells, appeared dysplastic and failed to display evidence of squamous differentiation. By comparison with primary oesophageal epithelial cells, the HET‐1A cells were highly proliferative and did not express the epithelial markers E‐cadherin or CK5/6 (casein kinase 5/6), or the stratified epithelial marker ΔNp63, but did express the mesenchymal markers vimentin and N‐cadherin. Conclusion. Studies of epithelial carcinogenesis will benefit from culture systems which allow manipulation of the stromal and epithelial layers independently. We have developed an organotypic culture using primary oesophageal squamous cells and fibroblasts in which a stratified epithelium with a proliferative basal layer that stains strongly for ΔNp63 develops. This model will be suitable for the study of the molecular events in the development of Barrett's oesophagus. The most commonly used normal oesophageal squamous cell line, HET‐1A, does not have the characteristics of normal oesophageal squamous cells and should not be used in models of the normal oesophageal epithelium. Until more representative cell lines are available, future studies in oesophageal cancer will be reliant on the availability and manipulation of primary tissue.